Disabilitas Menurut al-Quran: Tafsir Kontekstual QS. ’Abasa (80) : 1-10 - Anshori (Jalsah : The Journal of Al-quran and As-sunnah Studies, 2022)
This paper examines disability according to the Qur'an in QS. ‘Abasa (80): 1-10 which is focused on the term a’m? (blindness). The purpose of this study was to determine the meaning of QS. 'Abasa (80): 1-10 at the time of revelation which was then associated with the present context. The author uses a qualitative research method of library research type, which collects related data and then elaborates and then analyzes it (descriptive-analysis). The theory used is Abdullah Saeed's contextual interpretation theory, which in the process tries to reveal the meaning of the verse at the time of revelation (macro 1) and the contextual meaning of the verse (macro 2). The results show that there are three meanings of QS. 'Abasa (80): 1-10 that need to be known and applied in contemporary times. First, is the right to equality that should be realized for people with disabilities as obtained by other communities. Second, attention to literacy or learning rights should be given to people with disabilities. Third, rights are considered as part of society that can exist and have the same potential to take part in activities related to social society.